The Relationship Between Head Motion Synchronization and Empathy in Unidirectional Face-to-Face Communication - Yokozuka, Takahiro; Ono, Eisuke; Inoue, Yuki; Ogawa, Ken-Ichiro; Miyake, Yoshihiro (Frontiers in Psychology, 2018)
Embodied synchronization is widely observed in human communication, and is considered to be important in generating empathy during face-to-face communication. However, the quantitative relationship between body motion synchronization and degree of empathy is not fully understood. Therefore, we focused on head motion to investigate phase and frequency differences in head motion synchronization in relation to degree of empathy. We specifically conducted a lecture-based experiment using controlled spoken text divided into two parts: high empathy and low empathy. During the lecture, we measured the acceleration of speakers’ and listeners’ head motions using an accelerometer, and calculated the synchronization between the time-series data from their acceleration norms. The results showed greater head motion synchronization during high empathy. During high empathy, the speakers’ head motions began before those of listeners’ in the medium (2.5 Hz to 3.5 Hz) and high (4.0 Hz to 5.0 Hz) frequency ranges, whereas the speakers’ head motions tended to start later than those of the listeners’ in the low (1.0 Hz to 2.0 Hz) and medium (2.5 Hz to 3.5 Hz) frequency ranges. This suggests that the degree of empathy is reflected by a different relationship between the phase and frequency of head motion synchronization during face-to-face communication.